Pre-implementation evaluation for an HPV vaccine provider communication intervention among primary care clinics. Issue 33 (5th August 2022) - Barnard, Juliana G.; Marsh, Rebekah; Anderson-Mellies, Amy; Williams, Johnny L.; Fisher, Michael P.; Cockburn, Myles G.; Dempsey, Amanda F.; Cataldi, Jessica R.
Highlights: Implementation science can improve uptake of HPV vaccine interventions. Clinics in places with high risk for HPV cancers, low vaccine uptake were identified. Clinic staff would implement an intervention aligned with guidelines and workflows. Adequate time, external support for data tracking would facilitate implementation. Abstract: Objectives: Interventions to improve health care provider communication about HPV vaccination can increase vaccine acceptance. Our objectives were to (1) identify clinics in locations with high HPV-associated cancer and low HPV-vaccination rates that would potentially benefit from dissemination of a proposed HPV Provider Communication intervention and (2) use qualitative interviews and a dissemination and implementation framework to assess readiness for change and fit of the HPV Provider Communication intervention to the context of these clinics. Methods: Local HPV-associated cancer and HPV vaccination rates were assigned to Practice-Based Research Network clinics using data from the Colorado Central Cancer Registry, the Colorado Immunization Information System, and the American Community Survey. Staff from 38 clinics located in areas with high numbers of adolescents not up-to-date for HPV vaccine and high rates of HPV-associated cancers were recruited for qualitative interviews. Interview questions used the Promoting Action on Research Implementation in Health Services (PARIHS) conceptual framework and addressed the proposed intervention, current vaccination practices and prior quality improvement (QI) experience. Results: Twenty-seven interviews were completed with clinicians, clinic managers, and other staff across 17 clinics (9 pediatric, 5 family medicine, 3 public/school-based health). Most clinics had some prior QI experience and there were few thematic differences between sites with more or less foundation for QI/immunization work. Participants were motivated to improve the health of their patients and valued both guidelines and local experience as important evidence to consider adopting an intervention. Interviewees were more interested in implementing the proposed intervention if it aligned with existing priorities and fit within clinic workflows. Facilitation needs included adequate time and external facilitation support for data tracking and analysis. Conclusions: Qualitative interviews to understand clinic context and fit of an HPV Provider Communication intervention can inform implementation in settings with the highest potential for clinical impact.